Dynasties of Russian Storytellers in Yakutia and the Features of Their Repertoire (Bylinas and Historical Songs as a Case-Study) - Charina, Olga Iosifovna (Journal of History Culture and Art Research, 2018)
The article studies the traditional family features of Russian folklore in Yakutia of the Russian people living in an area near the mouth of the Kolyma River, the Indigirka River and the midstream of the Lena River. Within the scope of research on the general outline of Russian folklore distribution in Yakutia during its period of flourishment, we also overview the local features which were established in the course of an extended time-period; a number of example will be presented from epic texts created in the following areas: Biryuk of the Olyokminsky region, Pohodsk and Russkoye Ustye located on the shore of the Arctic Ocean. Written records by V.G. Bogoraz compiled at the end of the 19th century, the written records compiled by S.I. Bolo, N.A. Gabyshev at the early 1940s, and written records created by Y.I. Smirnov in the early 1980s. We will also refer to our own written records collected in the indicated northern areas where Russian folklore developed in the 1990s. These texts contain the same storytelling traditions which manifested themselves earlier in the bylinas about Ilia Muromets and the historical song entitled A Brave Man Beckons a Young Woman to Come to Kazan; each of these folklore texts were created in different time-periods: the end of 19th century and the middle/end of the 20th century correspondingly. The article also specifies the features represented in the folklore texts by M.F. Sokovikov, S.P. Kiselyov, E.S. Kiselyov, F.E. Sedyh. The study represents a comparative analysis of genres and plots along with some epic text motifs recorded in the written text in the midstream area of the Lena River, and the areas of the Kolyma and the Indigirka Rivers. There is a clear dynasty type of the epic texts inheritance visible in throughout the texts. The Sokovikovs (living in the 19th century in the Kolyma region) have practically lost their family traditions, whereas the Kiselyovs (a father and son) living in the 20th century in the Russkoye Ustye managed to remember a large collection of bylinas that they wrote down. The Sedyh family living in the midstream Lena River area managed to preserve an insignificant amount of epic texts due to the fact that this folklore genre was not wide-spread in the area.